2020
DOI: 10.36570/jduhs.2020.1.912
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Factors Associated With Dental Caries In Pregnant Females Visiting Antenatal Clinic of Public Sector Hospital of Karachi, Pakistan

Abstract: Pregnant women of age 18-45 years visiting antenatal clinic were included. The dental examination was carried out to assess the dental caries in accordance with the WHO diagnosis criteria. Frequency of dental caries along with factors like age, socioeconomic status, educational status, occupation, BMI, residence, family structure, gestational hypertension, and gestational diabetes were noted. SPSS version 23 was used to analyze data. The univariate logistic regression was applied to identify the significant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…In terms of chronic systemic diseases, such a diabetes mellitus, cardiovascular diseases, and hypertension, Azfar et al reported that hypertension and gestational diabetes were positively correlated with dental caries in pregnant women in which gestational diabetes was found to cause enamel defects in newborns of diabetic women [ 27 ], which was inconsistent with our results indicating the lack of a significant relationship between DMFT index and these diseases.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of chronic systemic diseases, such a diabetes mellitus, cardiovascular diseases, and hypertension, Azfar et al reported that hypertension and gestational diabetes were positively correlated with dental caries in pregnant women in which gestational diabetes was found to cause enamel defects in newborns of diabetic women [ 27 ], which was inconsistent with our results indicating the lack of a significant relationship between DMFT index and these diseases.…”
Section: Discussioncontrasting
confidence: 99%